Bajapuik Tradition the Traditional Marriage in Minangkabau - Hafizatul Anisa; Aman Aman; Dyah Kumalasari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Bajapuikis a tradition of the Minangkabau people native to the Padang Pariaman area which is carried out in a traditional marriage process. Bajapuik is the custom of the Minang community in respecting the position of men from Padang Pariaman but not detrimental to women as the biological bundo in the rumah gadang. Bajapuik has become a mandatory tradition at wedding ceremonies in Padang Pariaman by picking up / buying the groom using money whose nominal value is determined by means of family congregation and traditional leaders. Writing this article aims to describe the cultural customs of marriage in Minangkabau with a focus on the study of the Bajapuik tradition in Padang Pariaman. The method used in writing this scientific article is a qualitative method with a descriptive approach.